Toripalimab in combination with Anlotinib for unresectable hepatocellular carcinoma after SBRT: A prospective, single-arm, single-center clinical study - Chen, Yongbiao; Hong, Hanyin; Fang, Wenzheng; Zhang, Xia; Luo, Huachun; Chen, Zhijian; Yu, Jianda; Fan, Weiqiang; Chi, Xiaobin; Peng, Yonghai (Frontiers in Oncology, 2023)
OBJECTIVE: Exposing tumor antigens to the immune system is the key to ensuring the efficacy of immunotherapy. SBRT is the main way to reveal the specifical antigens of tumors which can enhance the immune response. We aimed to explore the clinical efficacy and safety of Toripalimab combined with Anlotinib for uHCC after SBRT. METHODS: This is a prospective, single-arm, explorative clinical study. uHCC patients with an ECOG PS score of 0–1, Child–Pugh class A or B, and BCLC stage B or C were included and treated with SBRT(8Gy*3) followed by 6-cycle combinational therapy with Toripalimab and Anlotinib. The primary endpoint was progression-free survival (PFS) and the secondary endpoints were objective response rate (ORR), disease control rate (DCR), overall survival (OS), and incidence of treatment-related adverse events (TRAEs). Continuous variables were presented as medians and ranges. Survivals were studied with the Kaplan-Meier method. Categorical data were expressed as n (percentage). (ClinicalTrials.gov identifier: ChiCTR2000032533). RESULTS: Between June 2020 and October 2022, a total of 20 patients with intermediate-advanced uHCC were enrolled. All cases had multiple intrahepatic metastases, or macrovascular invasion, or both, among whom 5 cases with lymph node or distant metastases. Until September 2022, the median follow-up time was 7.2 months (range, 1.1-27.7 months). Median survival time could not be assessed at the moment, based on iRecist, median PFS was 7.4 months (range, 1.1-27.7 months), ORR 15.0%, and DCR 50.0%. 14 patients experienced treatment-related adverse events with an incidence of 70%. The overall survival rates at 18 months and 24 months were 61.1% and 50.9%, respectively. And the progression-free survival rates were 39.3% and 19.7%. Conclusion: Exposure of specific antigens of HCC via SBRT may improve the efficacy of combinational therapy with Toripalimab and Anlotinib for uHCC with manageable adverse effects, which deserves further exploration.